(untitled) (International Journal of Studies in Nursing, 2022)
COVID-19 broke out in Wuhan in 2019, and spread rapidly around the world. More than 80% of COVID-19 patients are asymptomatic and non-severe, which may be an important source of infection. Therefore, the infectivity, clinical characteristics and outcome of such patients should be studied. The epidemiological data of 108 COVID-19 patients, as well as the clinical characteristics and treatment conditions of 100 asymptomatic and non-severe patients in Bozhou City, Anhui Province were collected. A retrospective analysis of the infectivity of asymptomatic patients was carried out, and a comparative study on clinical characteristics between asymptomatic patients and non-severe patients was also conducted. Eighty-six non-severe patients mainly had a cough (81.4%) and fever (70.9%), and only a few had the symptoms of upper respiratory tract infection such as sore throat (9.3%) and running nose (4.7%). Lymphopenia (20.9%) and elevated C-reaction protein (57.0%) were more frequent in non-severe patients compared with asymptomatic patients which were 0% and 14.3%, respectively. Among 100 asymptomatic and non-severe patients, 84 patients showed abnormal findings on the first chest CT, but meanwhile, 19 patients showed negative results on the viral RNA test. In 14 asymptomatic patients, five had lung abnormalities, which were all pure ground glass opacity. Eleven patients were infected by two asymptomatic patients; in the whole course of the disease, the two patients remained asymptomatic, but chest CT showed multifocal GGO. The time for clearance of SARS-CoV-2 in 12 patients taking methylprednisolone was longer than in other patients (21.2 d vs. 16.4 d). During follow-up, lung lesions found by chest CT in 58.3% of patients completely disappeared. Asymptomatic patients with abnormal chest CT were highly infectious, so SARS-CoV-2 RNA test, combined with a chest CT scan, could discover asymptomatic patients with strong infectivity. The application of glucocorticoids might lengthen the clearance time for SARS-CoV-2 RNA. Both asymptomatic and non-severe COVID-19 patients showed a better prognosis.